(untitled) (Comparative Professional Pedagogy, 2022)
The study of foreign experience is a prerequisite for innovative reform of teachers’ professional training. The purpose of the article is to analyze the Australian experience of preparing masters of education in multicultural educational context. The determined purpose of the study led to the formulation and solution of the two tasks. The first one is to find out the requirements for the knowledge, abilities and skills of teachers necessary to work in multicultural context of Australia. The second is to explore ways for improving the quality of teachers’ training to meet the educational needs of mastering intercultural competence (based on learning foreign languages) and intercultural communication. It is determined that the professional training of teachers of any specialty should be aimed at achieving three levels of intercultural competence. For our study, it is important to focus on the multicultural specifics of Australian society, as students in Australian schools demonstrate a variety of cultural learning needs. The peculiarities of training masters of education in Australia to perform their duties in the multicultural educational context are studied. The requirements for a teacher’s knowledge, abilities and skills to meet educational needs under the conditions of cultural diversity are clarified. The content of master’s programs and their compliance with the National Professional Standards for Teachers are analyzed. Finally, professional teacher training and its focus on the development of intercultural competence are described. A study of instructional documents on the training and further development of Australian teachers shows that the professional qualities and professional competencies they must possess to ensure effective work in a culturally diverse environment are reflected in Australian Professional Standards for Teachers. As a result of the analysis of the content of master’s degree programs at five leading universities in Australia, it is determined that, as a rule, programs meet the requirements of these professional standards, in particular in the context of the formation of intercultural competence.